Nanocomposites with biodegradable polymers synthesis, properties and future perspectives - Mittal, Vikas (Oxford : Oxford University Press, 2011)
Polymers are used in practically every facet of daily life. Most polymers come from fossil fuels and are not biodegradable causing long-term environmental hazards. Biodegradable polymers provide an alternative class of materials. Composites of such polymers have high potential within a wide spectrum of applications.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Polymers -- Biodegradation; Nanocomposites (Materials)